Analisis Faktor-Faktor Yang Menentukan Pertumbuhan Laba Dengan Corporate Governance Sebagai Variabel Pemoderasi: (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di ISSI Periode 2018-2020) - Ulfi Aprianingrum (Profesional Muda Cendekia Publishing, 2022)
This study aims to determine the effect of Current Ratio, Debt to Asset Ratio, Total Asset Turnover, Net Profit Margin, and Return on Assets on Profit Growth with Corporate Governance as Moderating Variable. This research is a quantitative research. Data were obtained from manufacturing companies registered with ISSI for the 2018-2020 period. The population obtained is 186 companies. The sample used in this study were 62 companies with purposive sampling method. The analytical tools used are multiple linear regression and Moderated Regression Analysis (MRA). The data processing tool uses Eviews 9. The results of this study indicate that the current ratio, debt to asset ratio and corporate governance have no effect on profit growth, return on assets has a significant and negative effect on profit growth, while total asset turnover and net profit margin have a positive and significant effect. to profit growth. Corporate governance can moderate the relationship of return on assets to profit growth, but cannot moderate the relationship of current ratio, debt to asset ratio, total asset turnover and net profit margin to profit growth.